2019
DOI: 10.1057/s41599-019-0275-0
|View full text |Cite
|
Sign up to set email alerts
|

Effective participatory science education in a diverse Latin American population

Abstract: Particular challenges exist for science education in the developing world, where limited resources require curricula designed to balance state-of-the-art knowledge with practical and political considerations in region-specific contexts. Project-based biology teaching is especially difficult to execute due to high infrastructural costs and limited teacher training. Here, we report the results of implementing short, challenging, and low-cost biology courses to high school and college students in Bolivia, designe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 52 publications
0
45
0
Order By: Relevance
“…The case of Bolivia is of particular interest, as it is the only country in which this compound was not only authorized by the PLA, but also massively produced by universities and distributed across the population (King, 2020;Trigo et al, 2020). Previous studies have shown that trust in alternative medicine is related to the lack of scientific literacy combined with misinformation (Ferreira et al, 2019;Lobera and Rogero-Garcia, 2020). Despite significant investments in education, Bolivia consistently ranks last in the region in science, technology and innovation production and its education system is heavily influenced by traditional and nonscientific curricula (Carosso et al, 2019;Ferreira et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case of Bolivia is of particular interest, as it is the only country in which this compound was not only authorized by the PLA, but also massively produced by universities and distributed across the population (King, 2020;Trigo et al, 2020). Previous studies have shown that trust in alternative medicine is related to the lack of scientific literacy combined with misinformation (Ferreira et al, 2019;Lobera and Rogero-Garcia, 2020). Despite significant investments in education, Bolivia consistently ranks last in the region in science, technology and innovation production and its education system is heavily influenced by traditional and nonscientific curricula (Carosso et al, 2019;Ferreira et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that trust in alternative medicine is related to the lack of scientific literacy combined with misinformation (Ferreira et al, 2019;Lobera and Rogero-Garcia, 2020). Despite significant investments in education, Bolivia consistently ranks last in the region in science, technology and innovation production and its education system is heavily influenced by traditional and nonscientific curricula (Carosso et al, 2019;Ferreira et al, 2019). Combined with a clear political and communication agenda, this situation led to the extensive use of chlorine dioxide in the country (Trigo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…GI and GII are unrelated, as countries like the United States and China with a relatively unequal societies, rank high in GII, due to their strong science agencies and research facilities. Latin American countries, on the other hand, consistently rank among the worst performers in this index (Crespo and Crespo, 2016;Ferreira et al, 2019). Science literacy and education are anticorrelated to pseudoscientific beliefs in the population (Carosso et al, 2019).…”
Section: The Reasons Behind Chlorine Dioxide Consumption In Latin Americamentioning
confidence: 95%
“…Previously, the Global Innovation Index (GII) has been used to assess the degree of science literacy in a population (Filho and Heerdt, 2018;Ferreira et al, 2019). GI and GII are unrelated, as countries like the United States and China with a relatively unequal societies, rank high in GII, due to their strong science agencies and research facilities.…”
Section: The Reasons Behind Chlorine Dioxide Consumption In Latin Americamentioning
confidence: 99%
“…Ideally, these latter would be seeking to boost their STEMrelated research so that they could match the senior academic landscape among developed countries with a prolonged and prosperous history of research and development (Kremer et al, 2013;Serpa et al, 2018;Eilks and Hofstein, 2014;Knamiller, 1984). One means to this end -and not exclusive to this end, either -would be to develop STEM education, which proved to be both useful and challenging (Ferreira et al, 2019). In fact, in a list of the Sustainable Development Goals (SDGs), the United Nations has highlighted the importance of high-quality education as foundational to sustainable development (United Nations).…”
Section: Introductionmentioning
confidence: 99%